-8(-8+a)=2(a+7)

Simple and best practice solution for -8(-8+a)=2(a+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(-8+a)=2(a+7) equation:



-8(-8+a)=2(a+7)
We move all terms to the left:
-8(-8+a)-(2(a+7))=0
We add all the numbers together, and all the variables
-8(a-8)-(2(a+7))=0
We multiply parentheses
-8a-(2(a+7))+64=0
We calculate terms in parentheses: -(2(a+7)), so:
2(a+7)
We multiply parentheses
2a+14
Back to the equation:
-(2a+14)
We get rid of parentheses
-8a-2a-14+64=0
We add all the numbers together, and all the variables
-10a+50=0
We move all terms containing a to the left, all other terms to the right
-10a=-50
a=-50/-10
a=+5

See similar equations:

| 20=-2(3x-1 | | 8+6=x-7 | | 2.5x+35x=100 | | -8(-6+3n)-3n=6(-4n+4) | | 15.9z-17.3=18.9z+19.6 | | 4-2n=8-n | | 3x-2=-28+3x | | 3/5(x+4/3)=1.041 | | 5x+6-10+3x=20-26 | | 100-35x=2.5 | | n/5-4=0 | | .25x=750 | | -16-11t=20-9t | | v-16=1 | | -8g=-5g-9 | | 9d-4d-d-9-3d=0 | | y/4*10=-14 | | 4x-3=-2x-2 | | –2k+6=–k | | -17=2u-5 | | 32=-4(y+-4) | | -4(6x-7)-8x=9x-300 | | t+3/8=7 | | 2(10+i)=20.5 | | 19=12+7(x-3) | | 3x+25=2x+40 | | x-4-3=-10 | | 4x-2+8-2x=10+12 | | -8.9s-11.97+0.75=18.87-7.2s | | x/5=1.33 | | 3x+19=3x-1 | | a-19=-20 |

Equations solver categories